HAK NAFKAH ISTRI DAN ANAK YANG DILALAIKAN SUAMI DALAM PERSPEKTIF HUKUM ISLAM DI DESA TETER KECAMATAN SIMO KABUPATEN BOYOLALI - Napsiyah, Siti; Syamsudin , Syamsudin; Baehaqi, Baehaqi (IBLAM LAW REVIEW, 2024)
This research aims: find out the typical husband who neglects his obligations towards his wife and children according to Islamic law, find out the factors of a husband who neglects his obligations toward his wife and children, find out the Islamic law for a husband who neglects his obligations toward his wife and children, find out the right to support the wife and children who are neglected by the husband in perspective of Islamic law in Teter Village Simo District Boyolali Regency.The approach taken is a qualitative approach, which means the data collected comes from interviews, observation, and documentation. Data analysis techniques used are data collection, data reduction, data presentation, and drawing conclusions.   The method used in this study is a survey method by taking information directly to respondents using a questionnaire it can provide a more realistic picture of the right to support a wife and children who are neglected by the husband in Teter village, Simo district Boyolali regency.  Respondents in this study are 12 couple of husband and wife in Teter Village Simo District Boyolali Regency.The right to support his wife and children in Teter village Simo District Boyolali. It is known that the category of husbands neglecting to support their wives and children includes husbands who do not protect, do not provide education, do not provide maintenance and clothing, do not provide housing, and do not provide living expenses or care higher percentage of 82 % compared to the percentage of fulfilling a living which is only 18 %. A percentage of 82 % is very negligent. There are internal and external factors that cause husband to neglect their wife and children, external factors consist of education and religious factors. Wife the internal factors are in the form of morals and patterns of parental guidance and education. The review of Islamic law based on the results of the above research is that husbands are very neglectful of family maintenance. In Islamic law, a husband who intentionally neglects his obligation to provide for his family is punished with sin.